Coaxial Germanium Lithium-Drifted Gamma Radiation Detectors - Wall, Basil (My University, 1966)
This thesis deals with the theory, fabrication and application of semi-conductor detectors to gamma ray spectroscopy. The theory section discusses the semi-conductor lattice with respect to the incoming gamma ray and the subsequent hole-electron pairs formed in the diode depletion region. The fabrication section describes the materials and apparatus used in this work to produce the Ge(Li) detectors. A table is given showing the characteristics of these devices as they proceed through the process. The section on the characteristics of these detectors gives information as to how a good detector should operate under certain tests., The detectors made in this laboratory were used to investigate a well known "fission product" nuclide and a neutron capture reaction on a rare earth element. However, these investigations were not exhaustive but only show how the improved resolution of the Ge(Li) detectors has opened up new areas of gamma ray studies.
Germanium Lithium-Drifted Detectors
This thesis is missing page 36, all other versions of the thesis are missing this page as well. -Digitization Centre
Keywords: germanium; lithium; gamma radiation detector; gamma radiation